Critical Thinking Skills of Junior High School Students in Science Learning - Yanih Maryani; Prasetyorini Prasetyorini; Irvan Permana (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2021)
Critical thinking skills are part of the 21st-century skills that are important for students to have. Critical thinking skills as an asset for students to achieve success in life. The purpose of this study is to describe the critical thinking skills of a state junior high school student in Bogor in learning Science. This research is a qualitative descriptive study. The research sample was taken by purposive sampling on the seventh-grade students of a state junior high school in Bogor. The participants were 176 students consisting of 81 boys and 95 girls. The data were collected by giving a multiple-choice test with the open reason, which was developed based on the indicators of the critical thinking skills of Ennis and interviews with a science teacher. The data were processed using Microsoft Office Excel 2013, then analyzed descriptively and qualitatively. The data analysis resulted in as many as 1.70% of students being included in the critical category; 88.64% of students are in the less critical category, and 9.66% are in the far less critical category. It can be concluded that the critical thinking skills of seventh-grade junior high school students in Bogor are still low at an average of 53.07. This proves that students' critical thinking skills still need to be trained further so that they can be improved.